EFEKTIFITAS BUZZ GROUP DAN PENDEKATAN INDIVIDUAL DALAM UPAYA PENCEGAHAN PNEUMONIA PADA BALITA - Sudarwati Nababan; Ariyanto Ayupir; Magdalena Bota Souisa (Jurnal Kesehatan Masyarakat, 2022)
In 2018, the province of East Nusa Tenggara ranked first in the highest prevalence of pneumonia, in Indonesia, which was 8.8%.  Toddlers with a history of cough were 2.64 times more likely to have pneumonia.  The data from Nelle Health Center showed that the number of toddlers who were treated with a cough diagnosis increased in 2019. In the COVID-19 pandemic situation, health education is directed at the counseling method. The purpose of this research was to compare the effectiveness of buzz group health education method with counseling to increase the knowledge, attitudes and behavior of mothers of toddlers.  This research method is quasi eksperimen nonequivalent control group. The research sample was 60 mothers from Manubura village divided into 2 experimental groups, and 30 mothers from Nelle Urung village as control group. Collecting data using an interview guide questionnaire, posttest is done after one month of health education. Health education is carried out once for 20 minutes. The effectiveness of the method is known after analyzing the data using the Manova test. There were significant differences in knowledge, attitudes, and behavior before and after health education in the buzz group and counseling group method when compared to the control group. Health education using the buzz group and counseling method were equally effective in increasing mother's knowledge (p=0.422) and mother's attitude (p=0.306) about pneumonia. Buzz group health education method is more effective in improving mother’s behavior in preventing pneumonia than counseling method, the average difference is 2.20 score. This difference in behavior is due to different methods of health education. Buzz group health education is a horizontal health education with adult learning.